PENGARUH IMPLEMENTASI TOTAL QUALITY MANAGEMENT, SISTEM PENGUKURAN KINERJA, DAN SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL (Studi pada Biro Perjalanan Wisata di Kota Semarang) - Ramadhan Noor Rachman Fatoni; Mahfudz Mahfudz (JURNAL STUDI MANAJEMEN ORGANISASI, 2018)
Managerials play an important role in a company in determining the course of the company. The success of the company is measured through managerial performances. High managerial performance makes the success of the company is also getting higher. The purpose of this study is to analyze the effect of the implementation total quality management, performance measurement system, and reward on managerial performance.            The population in this study are the managerial ranks at the Travel Berau of the Semarang City. This study was conducted by distributing questionnaires to a sample of 90 respondents using simple random sampling method. Data analysis method used in this study is multiple linear regression analysis with SPSS version 23th.            The result showed that total quality management, performance measurement system, and reward system had a positive and significant effect on managerial performance.In the study found the regression equation as follows: Y = 0.340 X1 + 0.266 X2 + 0.319 X3. Total quality management has the most significant influence on managerial performance with a coefficient of 0.340. The performance measurement system has the lowest significant influence in this study with a coefficient of 0.266